1D behind the scenes - Delmege, Sarah; Harris, Simon (Harper, 2011)
Packed with never-before-seen photos, exclusive interviews, and fascinating facts, you'll find everything you ever needed to know about Harry, Niall, Liam, Louis, and Zayn inside! A must-have for every One Direction fan!